Effectiveness of Trainings of General Practitioners on Antibiotic Stewardship: Methods of a Pragmatic Quasi-Experimental Study in a Controlled Before-After Design in South-East-Lower Saxony, Germany (WASA) - Gornyk, Daniela; Scharlach, Martina; Buhr-Riehm, Brigitte; Klett-Tammen, Carolina Judith; Eberhard, Sveja; Stahmeyer, Jona Theodor; Großhennig, Anika; Smith, Andrea; Meinicke, Sarah; Bautsch, Wilfried; Krause, Gérard; Castell, Stefanie (Frontiers in Pharmacology, 2021)
Antibiotic resistance is a serious threat to global public health. It reduces the effectiveness of treatments for serious bacterial infections and thus increases the risk of fatal outcomes. Antibiotic prescriptions are often not in line with clinical evidence-based guidelines. The process of emergence of resistant bacteria can be slowed down by adherence to guidelines. Yet this adherence seems to be lacking in primary health care. This pragmatic quasi-experimental study using a controlled before-after design is carried out in South-East-Lower Saxony in 2018 - 2020. The voluntary attendance of interactive trainings with condensed presentation of current guidelines for general practitioners (GP) on antibiotic management for urinary and respiratory tract infections is regarded as intervention. Those GP not attending the trainings constitute the control group. Data are collected via questionnaires; routine health records are provided by a statutory health insurance. The primary outcome is the proportion of (guideline-based) prescriptions in relation to the relevant ICD-10 codes as well as daily defined doses and the difference in proportion of certain prescriptions according to guidelines before and after the intervention as compared to the control group. Further outcomes are among others the subjectively perceived risk of antibiotic resistance and the attitude towards the guidelines. The questionnaires to assess this are based on theory of planned behavior (TPB) and health action process approach (HAPA). Variations over time and effects caused by measures other than WASA (Wirksamkeit von Antibiotika-Schulungen in der niedergelassenen Aerzteschaft - Effectiveness of antibiotic management training in the primary health care sector) training are taken into account by including the control group and applying interrupted time series analysis. The study protocol and the data protection concept respectively were reviewed and approved by the Ethics Committee of the Hannover Medical School and the Federal Commissioner for Data Protection and Freedom of Information. Findings will be presented on scientific conferences and in peer-reviewed scientific journals. Trial registration number: DRKS00013951. Registered 21 January 2019. Retrospectively registered. URL: https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00013951